Proceeding of Experimental Hypercholesterolemia After Cryopreserved Hepatocyte Allotransplantation - Lebedinskiy, A. S.; Petrenko, A. Yu.; Sukach, A. N. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of cryopreserved hepatocytes on lipid metabolism under allotransplantation to rabbits with experimental hypercholesterolemia (HC) was studied in this work. It was demonstrated, that the cryopreserved isolated hepatocytes were capable to cause a significant regulatory effect on lipid metabolism, but the noted effects were limited by the first week of observation. Â